Limb-girdle Muscular Dystrophy with New Mutation in Sarcoglycan Beta Gene: A Case Report - Eskandar TAGHIZADEH; Hamed ABDOLKARIMI; Reza BOOSTANI; Arianeh SADRNABAVI (Tehran University of Medical Sciences, 2018)
Limb-girdle muscular dystrophies (LGMDs) are a large group of genetic diseases in which there is muscle weakness and they are heterogonous diseases. The following study conducted in September 2017 in Mashhad, northwest of southern Khorasan Province, Iran reports a four years girl of autosomal recessive LGMD with proximal weakness and myopathy patterns. We detected four new alternations in this patient not reported for our population. One of them was important clinically that exists as unreported homozygous deletion encompassing exon 2 of the Sarcoglycan Beta (SGCB) gene. The use of Next Generation Sequencing (NGS) in the diagnosis of rare genetic pathologies is becoming ever more widespread in clinical practice. We used the NGS method for the first time to analysis the mutation in this family.